“Orthoglossopelveplasty” and the algorithm for its use in the Pierre Robin sequence - Vera Lúcia Nocchi Cardim; Jullyana Heinen Peixoto; Alessandra dos Santos Silva (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Several patients with the Pierre Robin sequence (micrognathia, glossoptosis, and airway obstruction) have an altered, shortened, and retractable genioglossus muscle that prevents protraction of the tongue and keeps the anterior part of the tongue vertical and its volume posteriorly displaced. This can contribute to supraglottic obstruction, feeding difficulty, and inversion of the growth stimulation forces of the mandibular body. Methods: A retrospective study of patients with the Pierre Robin sequence treated between 2012 and 2017 with "orthoglossopelveplasty," which includes modification of glossopexy, releasing the anomalous genioglossus of its insertion and releasing the tongue to raise its anterior third and advance the volume of its base using a traction suture of the tongue base to the mandible symphysis. We present a treatment algorithm that prioritizes the need for surgery associated, or not, with mandibular distraction in accordance with respiratory and/or feeding difficulty severity. Results: Twelve cases of oropharyngeal obstruction treated from 2012 to 2017 are presented, their priorities and orthoglossopleoplasty are discussed, and the proposed algorithm is applied. Conclusion: Anatomical reorganization of the musculature in a correct anterior position provides protraction and functionality to the tongue, clears the airway in the oropharynx, and improves the feeding function and mandibular development, with low surgical morbidity rates and few complications.